Digital Biomimetic Architecture between Art and Dynamic Structure: Case Study—Wings in Flight - Shih, Shen-Guan; Huang, Yen-Fen; Wagiri, Felicia; Wu, Shi-Yen (Complexity (New York, N.Y.), 2020)
Architecture as a multirelated field is influenced and connected by many subjects. Among those subjects, the role of art and natural science is the most dominant frame without ignoring the development of advanced technology. By using technology, the impossible becomes possible such as to capture the body motion of humans as the subject of art and science at the same time. Body motion is a potential research of movement over the time. This does not only involve the aesthetic, but also even more the scientific aspect of a dynamic motion of an organism that can be investigated through a biomimetic approach. In order to understand the biomimetic term, we investigated the physical morphogenesis and geometrical principle of an organism. The term morphogenesis is a process in which the natural system produces and regulates the configuration of a material in space and over time. Based on that, we tried to design a dynamic structure using butterfly’s motion as a subject of study with morphological and biomimetic approaches. Butterflies show a simultaneous aspect of movement over time characterized by fragmentation. This idea also summarizes many aspects of modern art such as portrayal of body movements by futurists, space-time continuum, cinematic freeze frame, and time-lapse photography. A futurist represents a movement that is emphasized on the factors of speed, technology, modernisms, and objects. This indicates an alternative position that may be relevant to the system of butterfly wings. This can only be achieved by utilizing a digital design and its parametric tools that help generate functions and form dynamic structures with high complexity and precision. Throughout the development of the system, there will be many changes to the form which will be constantly tested and evaluated using a series of prototype and visual digital design.